Associations between common mental disorders and sexual dissatisfaction in the general population. (2nd January 2018) - Vanwesenbeeck, Ine; ten Have, Margreet; de Graaf, Ron
Abstract : Background: Little is known about the associations between common mental disorders and sexual dissatisfaction in the general population. Aims: To assess the associations between the presence of 12-month and remitted (lifetime minus 12-month) mood, anxiety and substance use disorders and sexual dissatisfaction in the general population of The Netherlands. Method: A total of 6646 participants, aged 18–64, took part in a face-to-face survey using the Composite International Diagnostic Interview 3.0. Childhood trauma, somatic disorders and sexual dissatisfaction were also assessed in an additional questionnaire. Associations were assessed with multivariate regression analyses. Results: In total, 29% reported some sexual dissatisfaction. Controlling for demography, somatic disorders and childhood trauma, significant associations with 12-month mood disorder (B = 0.31), substance use disorder (B = 0.23) and anxiety disorder (B = 0.16) were found. Specifically, relatively strong associations were found for alcohol dependence (B = 0.54), bipolar disorder (B = 0.45) and drug dependence (B = 0.44). The association between remitted disorders and sexual dissatisfaction showed significance for the category substance use disorder. Conclusions: People with mood, anxiety and substance use disorders show elevated scores on sexual dissatisfaction, even when relevant confounders are controlled for. Sexual satisfaction appears to be reduced most by alcohol and drug dependence and bipolar disorder. Once remitted, substance use disorder shows a persisting association with present sexual dissatisfaction.